Pembelajaran Matematika Integratif Bernuansa Islam Melalui Project-Based Learning Pada Materi Geometri Dengan Konteks Fikih - Ulum, Moh. Miftakhul; Annisa, Hurriyatul; Hasan Asnawi, Muhammad; Laili Arofah, Nur (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2021)
It should be realized that research on the integration of mathematics with Islam is numerous and varied. However, if explored more deeply related to research on how to teach integrated mathematics with Islamic nuances, it is still lacking. Therefore, this article will provide an idea or description of what teachers can do to teach mathematics integrated with Islamic values. This article aims explicitly to combine integrative mathematics learning with Islamic nuances with the Project-Based Learning model, namely on the volume material of cubes and blocks with the context of the two Gullah water fiqh. The research approach used in this research is qualitative with the type of literature study. This research was conducted by looking for theoretical references that are relevant to the problems found. The data is obtained from articles, books, and other documents that can describe the theory and information needed. The steps for implementing Project-Based Learning are as follows: 1) determining fundamental questions, 2) designing project plans, 3) compiling a project completion schedule, 4) monitoring project progress, 5) testing project results and 6) evaluating learning experiences. In conclusion, integrative mathematics learning with Islamic nuances can be combined with the Project-Based Learning model. The hope to be achieved is that, on the one hand, it can increase motivation to learn mathematics, but on the other hand, it can also hone the ability to analyze the problems that exist in religious life, especially Islam.